Pengaruh Transparansi, Akuntabilitas, dan Partisipasi Masyarakat Terhadap Pengelolaan Dana Desa (Studi Kasus Pada Desa di kecamatan Secanggang, Kabupaten Langkat) - Lause, Vinna Syndi; Iqlima Azhar; Agustina Nurul Fajriah (Ali Institute of Research and Publication, 2024)
This research aims to examine the influence of transparency, accountability and community participation on village fund management in villages in Secanggang sub-district, Langkat district. This type of research uses quantitative methods. The data used in this research is primary data by distributing questionnaires. The total population and research sample 64 people. The sample in the study used a saturated sample. The data analysis method used is the multiple regression method, the classic assumption test, validity test method, reliability test, normality test, multicollinearity test, heteroscedasticity test, descriptive statistics and f test, t test and coefficient of determination test. The result of t test showed that transparency has a value of 0,94>0,05 means that transparency has no effect on the management of village funds. The accountability variable has a value of 0,000<0,05 meaning that accountability has a positive and significant effect on village fund management. The community participation has a value of 0,04<0,05 meaning that community participation has a positive and significant effect on village fund management. The F test results obtained were 0,000<0,05. This shows that transparency, accountability, and community participation simultaneously have a positive and significant effect on village fund management. Based on the results of the coefficient of determination test, it was found that 81% of the dependent variable could be explained by the independent variable, while the remaining 19% was influenced by other factors not examined in this research.